High perfomance audio power amplifiers for music performance and reproduction - Duncan, Ben (Newnes, 1996)
Linking analog electronics, acoustics, heat and music technology; high-end hi-fi and professional PA and recording studio use; theory, modelling and real-world practice; design and repair; the old and the new, the mainstream and the specialised, this comprehensive guide to power amps is a core reference for anyone in the industry, and any interested onlookers